Patronage factors of Tabung Haji among Muslim community in Kampung Gajah, Perak / Nurul Khairoh Mohd Yasir @ Mohd Nasir - Mohd Yasir @ Mohd Nasir, Nurul Khairoh (2021)
Islamic financial institutions play an important role in facilitating the flow of funds from the surplus unit to the deficit savings unit. They also play a role in generating profits through transactions that comply with Islamic principles of Shariah Law. Tabung Haji is one of the Islamic financial institutions providing very systematic facilities for the well-being of Muslims in performing hajj in Malaysia. the study aims to examine Patronage Factors of Tabung Haji Among the Muslim Community. This study was conducted among Muslim individuals in Kampung Gajah, Perak. Furthermore, this study also touched on the topic of saving money from Islamic and conventional views as well as the good of saving money and describes the activities of saving and withdrawing money carried out by the Tabung Haji. The purpose of this study was being conducted is to solve problems related to the main patronage factors of Tabung Haji among the Muslim community in Kampung Gajah, Perak. Previous studies have told about a pilgrimage's financial motives: lessons to be drawn from Tabung Haji Malaysia. The researcher will able to find out if the Muslims’ purpose in saving money in the Tabung Haji. Besides, there is also a study on religious value as the main influencing factor to customers patronizing Islamic banks. From this study, the researcher obtained information about the factors considered important by academic experts to the selection of banks. Thus, in this study, a researcher will report and determine the main factors that become the main factor of Muslims becoming regular customers in Tabung Haji to add the lack of information that has been reviewed by previous researchers. Respondent data will be obtained through an online questionnaire and also open-ended interviews of some respondents regarding the factors that influence depositors to keep saving money in Tabung Haji based on their opinions. The data obtained were analyzed and determined what are the factors that influence depositors either religious motivation or performance or quality of services or integrity. The results of this study also showed some suggestions towards Tabung Haji such as setting up sadaqah funds for future pilgrims who do not have enough money to perform hajj. In this way, it helps Tabung Haji in attracting depositors to keep interesting in Tabung Haji then in further improving the development of service aspects as well as the infrastructure of Tabung Haji. At the same time, Tabung Haji also contributed to the progress in the financial sector as well as improving the economic efficiency of the Islamic community in Malaysia.